“A Common Obsession”: Children’s and Young People’s Perceptions of Learning in an Intensive Summer Choral Program - Barrett, Margaret S.; Zhukov, Katie (Frontiers in Education, 2022)
This article reports the findings of an investigation of children’s and young people’s perceptions of learning and life outcomes, environmental supports and teaching and learning strategies encountered in an intensive summer choral program. Whilst the recognition of children’s and young people’s right to voice their perspectives was enshrined in the UN Convention on the rights of the child (1989), the music education profession has taken some time to foreground children’s and young people’s voice as a research focus. Initial investigations of music “student voice” have focused largely on school environments with fewer studies addressing youth music settings. The study addressed this gap through investigating children’s and young people’s perspectives of an intensive summer multi-level choral program (participants aged 11–24 years). Data were generated through extended semi-structured interviews with 11 choristers during the second and final week of the program. Stage One analysis identified 10 emerging themes and 31 sub-categories describing the experience of choral engagement. This was further refined through a Stage Two analysis against the five themes of a framework for understanding the meaning and value of music participation for children and young people in these settings, comprised of: (1) love of performance; (2) unity of purpose; (3) challenge and professionalism; (4) relationships and community; and (5) individual growth and well-being. Participants’ love of choral performance was supported across a virtuous cycle of choral engagement developed through being part of a motived cohort of like-minded “choir nerds” sharing a love of music and unity of purpose. Their appreciation of musical challenge and professionalism was evidenced in descriptions of intensive and demanding rehearsals focused on music detail and refining singing and general music skills. Key to their participation was a sense of being a member of an inclusive community with shared values for high standards of musicianship and performance, and connection with leading conductors and accompanists. Choristers reported individual growth and well-being citing increased singing and general music skills, increased confidence and independence, improved motivation, persistence and leadership skills, and, improved social skills including team-work and time-management skills.